Bilateral Subthalamic Nucleus Deep Brain Stimulation in Elderly Patients With Parkinson Disease: A Case‐Control Study. Issue 3 (September 2020) - Mitchell, Kyle T.; Younce, John R.; Norris, Scott A.; Tabbal, Samer D.; Dowling, Joshua L.; Rich, Keith M.; Perlmutter, Joel S.; Ushe, Mwiza
Abstract : BACKGROUND: : Subthalamic nucleus deep brain stimulation (STN DBS) is an effective adjunctive therapy for Parkinson disease. Studies have shown improvement of motor function but often exclude patients older than 75 yr. OBJECTIVE: : To determine the safety and effectiveness of STN DBS in patients 75 yr and older. METHODS: : A total of 104 patients (52 patients >75 yr old, 52 patients <75 yr old) with STN DBS were paired and retrospectively analyzed. The primary outcome was change in Unified Parkinson Disease Rating Scale (UPDRS) subscale III at 1 yr postoperatively, OFF medication. Secondary outcomes were changes in UPDRS I, II, and IV subscales and levodopa equivalents. Complications and all‐cause mortality were assessed at 30 d and 1 yr. RESULTS: : Both cohorts had significant improvements in UPDRS III at 6 mo and 1 yr with no difference between cohorts. Change in UPDRS III was noninferior to the younger cohort. The cohorts had similar worsening in UPDRS I at 1 yr, no change in UPDRS II, similar improvement in UPDRS IV, and similar levodopa equivalent reduction. There were similar numbers of postoperative intracerebral hemorrhages (2/52 in each cohort, more severe in the older cohort) and surgical complications (4/52 in each cohort), and mortality in the older cohort was similar to an additional matched cohort not receiving DBS. CONCLUSION: : STN DBS provides substantial motor benefit and reduction in levodopa equivalents with a low rate of complications in older patients, which is also noninferior to the benefit in younger patients. STN DBS remains an effective therapy for those over 75 yr. Graphical Abstract: Figure. Graphical Abstract